Effects of Membrane Covers and Biochar on Compost Quality and Greenhouse Gas Reduction in Aerobic Composting - Jie Cao; Haoli Qu; Ruirong Li; Pengjun Wang; Jingjing Fu; Mingjiang Chen (BioResources, 2024)
The addition of biochar and the use of membrane coverings are two methods used in aerobic composting of agricultural waste. The effectiveness of each of these two methods on compost quality and reduction of greenhouse gas emissions was tested in the laboratory. The results showed that both methods increased the maximum composting temperature and extended the thermophilic period. The germination index of biochar-treated compost and membrane-covered compost reached 70% on the 18th day, which was 12 days earlier than the corresponding value in the control group. The products from the biochar-treated compost had higher pH and lower electrical conductivity, compared with the product of the control group, indicating that these products are more suitable for acidic soils. In terms of greenhouse gas reduction, both methods were found to reduce the emissions of CH4 and N2O from composting. The addition of biochar had a better emission reduction effect on N2O, whereas the membrane covering technique yielded a better effect on CH4 emission reduction. The results of this study provide technical support for managed aerobic composting to reduce greenhouse gas emissions.